2016
DOI: 10.1128/genomea.01167-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Siphoviral Bacteriophage Ec-ZZ2, Which Is Capable of Lysing Enterococcus faecium

Abstract: A virulent bacteriophage (Ec-ZZ2) that infects Enterococcus faecium was isolated from sewage. The bacteriophage belongs to the family Siphoviridae and has a linear double-stranded DNA genome, with a length of 41,170 bp and a 34.59% G+C content, which is highly similar to Enterococcus phage IME-EF4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Electron microscopy observation demonstrated that the isolated phage belonged to the Siphoviridea family. Similar to our study Li et al isolated E. faecium-infecting Ec-ZZ2 phage with characteristics of the Siphoviridea family (30) .De- termining the hosting spectrum defines the biological characteristics of the phage and is a crucial step in phage therapy (31). The host range of our isolated phage was examined on 34 clinical VREfm strains by the spot test.…”
Section: Discussionsupporting
confidence: 71%
“…Electron microscopy observation demonstrated that the isolated phage belonged to the Siphoviridea family. Similar to our study Li et al isolated E. faecium-infecting Ec-ZZ2 phage with characteristics of the Siphoviridea family (30) .De- termining the hosting spectrum defines the biological characteristics of the phage and is a crucial step in phage therapy (31). The host range of our isolated phage was examined on 34 clinical VREfm strains by the spot test.…”
Section: Discussionsupporting
confidence: 71%